Permanent Tracheostomy Care and social Stigma in Nigeria - Jasper, Abiodun Oyinpreye; Okolugbo, Nekwu (International Journal of Psychosocial Rehabilitation, 2020)
Lifesaving therapies may sometimes require the surgical removal or interference with a normal body structure that is obvious to the people in the immediate social environment. These may elicit some unsavory reaction, from people around, causing adverse psychological effects on the patients concerned. Permanent tracheostomy is one of such surgical procedures; though intended to be life-saving, may end up being a permanent disability. Permanent tracheostomy is done for patients with permanent recurrent laryngeal nerve damage post-thyroidectomy, post- laryngectomy (due to oropharyngeal cancer), head and neck trauma and some neck cancers. Due to the small percentage of surgical, hospital attending patients needing tracheostomy, the special concerns of these patients have been easily overlooked. These group of patients have peculiar problems managing the tracheostomy, starting from prolonged hospital stay, and multiple hospital admission both contributing to their cost burden. Few publications have been done in our environment on the psychological impact on adults and children who end up with this surgery as in other climes. Outside the initial Problems of negative attitude of immediate family, speech difficulty and nonavailabilty of tracheostomy tube parts to enhance speech; Social stigmatization is a source of grave concern, which requires concerted efforts at rehabilitation and social re-integration. The travails of the permanent tracheostomy patient is mitigated, not only by highly skilled and specialized medical care; but also by advocacy groups for such a minority ailment: unlike sickle cell, hypertension, and diabetes that over time have become familiar to the populace. Advocacy groups can help in ensuring availability of tracheostomy accessories to aid speech, thereby making the tracheostomy patient attractive in the community and aiding meaningful social integration. This would make them a voice for the “voiceless”; to mitigate the effects of stigmatization and discrimination in the Nigerian society.